Strategies for Strengthening Safety Participation Through The Optimization of OHSMS and OHS Training - Fajar, Muhammad Kiflan; Abdurrahman Hakim (Jurnal Management Risiko dan Keuangan, 2025)
This study aims to analyze the influence of the implementation of the Occupational Health and Safety Management System (OHSMS) and OHS Training on safety participation among employees of PT Pejaten Jaya Abadi. A quantitative approach was employed, utilizing a survey method involving 140 employee respondents. The results of multiple linear regression analysis indicate that both OHSMS and OHS Training have a positive and significant effect on safety participation. The contribution of these two independent variables reaches 78.8% in increasing employee participation in workplace safety. These findings emphasize the importance of a structured OHSMS implementation and effective safety training in building a safety culture and enhancing employee engagement in occupational safety programs within construction companies. This study recommends that companies strengthen OHS policies and develop relevant training to reduce workplace accidents and create a safe and productive work environment.